Assessing different monoblock dielectric implementations of a low profile beam steering transmitarray for 3D printing - Teixeira, J.; Matos, S. A.; Costa, J. R.; Felício, J.; Fernandes, C. A. (2022 Microwave Mediterranean Symposium (MMS), 2022)
Transmit-arrays (TAs) can be a cost-effective solution for high gain steerable antennas using millimeter waves. For some applications these antennas can be a viable alternative to the extremely compact and agile phased-arrays counterpart. The main motivation is to reduce the high costs associated with the complex and lossy feeding networks of phased arrays - a fundamental factor when aiming for mass-market technology. Combining the flexibility of TAs with 3D printing can further enhance the low-cost potential of these antennas. This work focuses on apertures composed by a single dielectric material compatible with the affordable 3D printing technique, Fuse Deposition Modelling (FDM). However, the resulting aperture will be thicker and have higher losses comparing with printed circuit board (PCB) TAs. We show that, despite these limitations, the dielectric implementation of TAs performs well even for demanding designs. We present several dielectric realizations of a TA design capable of wide mechanical beam scanning (up 49 degrees) with a low profile (F/D=0.34) and 26 dBi maximum gain at 30 GHz. We assess how the performance of this antenna is affected by the way that the T A phase correction is crafted in the dielectric block.